Influence of Birth Order on Children’s Sense of Responsibility - Alfiana, Nokha; Rohmah, Naili (Universitas Negeri Semarang, 2025)
Every child born into a family has different genetic characteristics and is exposed to different social environments, including their birth order. Each child's attitude, personality, and behavior will be influenced by those factors. Within the family, the sense of responsibility of the eldest child, the middle child, and the youngest child will differ due to the differences they have as members of the social group. Therefore, it is necessary to examine this to find out the effect of birth order on children's sense of responsibility by taking samples from early childhood aged 5-6 years as the firstborn, the middle child, and the youngest child. This study used a quantitative-correlational method with questionnaires as data collection techniques. The results of this study obtained data and facts that the birth order process showed an influence in several aspects, such as children can respect time, obey the rules, return items according to their place, accept the risk of actions taken, protect their belongings, do not easily blame or accuse others, are willing to admit and apologize for mistakes made, and do activities before being directed or ordered. Birth order is proven to have a significant positive influence on children's sense of responsibility.